Diagnostic accuracy of Bronchoalveolar lavage fluid in diagnosis of lung cancers in a tertiary care hospital in coastal region of Karnataka - Dr. Medha Shankarling; Dr. Sunil Kumar Y; Dr. Shetty K Padma; Dr. Shetty Jayaprakash (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Bronchoalveolar lavage (BAL) fluid analysis helps in early detection, rapid diagnosis and treatment of lung cancer as the therapy is based on subtyping. BAL has an important role in diagnosis of peripherally situated bronchoscopically invisible primary lung cancers, most of which are adenocarcinomas. Purpose: This study aims to detect diagnostic accuracy of BAL fluid analysis in detection of lung cancers. Materials and Methods: This retrospective cum prospective study in a tertiary care hospital involved analysis of BAL fluid obtained by lavage of respiratory tract in clinically and radiologically suspected lung lesions for 4 years from January 2012 to December 2016. Results: Out of 169 BAL fluids received, 38(22.4%) were positive for malignancy. Squamous cell carcinoma is the most common cancer noted in our study. BAL was reported falsely negative for malignancy in 49 cases (56.7%) proved by lung biopsy. BAL was reported falsely negative for malignancy in 49 cases (56.7%) proved by lung biopsy. One false positive case was noted in our study. The sensitivity of BAL was 43% and specificity of BAL was 98.8% in our study. The positive predictive value of BAL in the diagnosis of lung cancers is 97.36%. The negative predictive value of BAL in the diagnosis of lung cancers is 62.59%.The diagnostic accuracy of BAL is 70.4%. Conclusion: BAL fluid analysis provides a rapid, reliable process to detect, subtype malignancies of the lower respiratory tract both in bronchoscopically visible and invisible tumours.